CuBr2-promoted intramolecular bromocyclization of N-allylamides and aryl allyl ketone oximes. Issue 48 (30th November 2017) - Yang, Chun-Hua; Xu, Zhong-Qi; Duan, Lili; Li, Yue-Ming
Abstract: A new and easy-to-perform route to 2-oxazolines amd isoxazolines was reported. Using CuBr2 as both the bromide source and the reaction promoter, bromocyclization of N-allylamides and allyl ketone oximes proceeded readily, leading to oxazolines and isoxazolines in good to excellent yields. Graphical abstract: